Forensic Discrimination of White Architectural Paints via ATR FT-IR Spectroscopy and Chemometrics - Sweety Sharma; Gurpreet Kaur; Chongtham Nimi; Rajinder Singh (Arab Journal of Forensic Sciences & Forensic Medicine)
The present work entailed the comparative examination and discrimination of white architectural paint samples of different brands/manufacturers. The analysis of this evidence can facilitate exhibiting a linkage between the victim, and the crime scene and assist in the reconstruction of the crime scene. Architectural paint traces have evidential value, especially in cases of burglary, acts of vandalism, property crimes, etc. In the present study, a total of 102 samples of 34 distinct brands (3 samples of each brand) of white commercially available architectural paints were purchased and analysed using ATR FT-IR spectroscopy and multivariate analytical tools. The use of visual analysis of FTIR spectral data resulted in 12 undifferentiated/indistinguishable sample pairs with a discrimination power of 97.86%. Adding PCA and PLS-DA in concert with visual analysis of FTIR spectra resulted in 99.4% (3 sample pairs undifferentiated) and 100% discrimination power, respectively. In conclusion, samples of each brand were completely differentiated using ATR FT-IR spectra subjected to the PLS-DA model. To assess the impact of different substrates on the examination of paint chips, simulated samples were produced on different substrates and the obtained results from the substrates study have been summarized. The ATR-FTIR spectroscopy therefore suggests an objective and rapid approach for the discrimination of white architectural paints for forensic purposes.